Exploration of Learning Community Models in Increasing Quality of Learning in the New Normal Era - Sulaiman Effendi; Henny Zurika Lubis; Fatmawarni Fatmawarni (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to explore the learning community model in accounting learning so that it can improve the quality of learning in the classroom. In the learning community focus on learning that ensures that students learn, a culture of collaboration, and learning outcomes oriented. This study uses a descriptive method, using research literature, expert reviews and needs analysis to find out what is in the field. The initial data collection used is observation, documentation studies, condition interviews, and questionnaires. Based on the results of the study that student learning outcomes have increased from 66.11% to 84.38% with an average increase in learning outcomes of 18.27% so this shows that learning with the learning community model makes students active by holding their respective roles. Each to exchange knowledge through virtual discussions making it easier for students to understand material that has an impact on improving student learning outcomes.